A comparison of men and women undergoing septoplasty—the Swedish national septoplasty register - Pedersen, Lars; Holmberg, Kenneth; Ahlström Emanuelsson, Cecilia; Schiöler, Linus; Steinsvåg, Sverre; Hellgren, Johan (Frontiers in Surgery, 2023)
Objective: Men represent more than two-thirds of septoplasty patients in many studies, but differences between men and women in terms of patient selection or outcome are seldom reported. This study aims to investigate whether women undergoing septoplasty differ from men in critical variables before and after surgery, in a large national sample of septoplasties. Design: Cross-sectional register study. Participants: The study includes 2,532 patients from the National Swedish Septoplasty Register undergoing septoplasty with or without additional turbinoplasty on the indication of nasal obstruction in 2014-2019. Patients in the register have not been preselected. Main outcome measures: Preoperative variables and postoperative outcome were compared between men and women. Results. Men accounted for 1,829 (72%) of the patients. There was no significant difference between men and women in severity of self-reported nasal obstruction or type of surgery performed (septoplasty with or without turbinoplasty). Mean postoperative nasal obstruction 12 months after surgery and overall satisfaction with the result were similar. Women, however, reported more complications 12 months postoperatively, while men reported more problems with snoring and obstructive sleep apnea preoperatively. Conclusion. In this large national patient cohort undergoing septoplasty, we found no differences in preoperative nasal obstruction or postoperative patient-rated outcome in men and women undergoing septoplasty, despite the fact that 72% of the patients were men. It thus remains unclear why women are under-represented in septoplasty surgery in this and many other cohorts.